Predictors of professional behaviour and academic outcomes in a UK medical school: A longitudinal cohort study. (2nd September 2015) - Adam, Jane; Bore, Miles; Childs, Roy; Dunn, Jason; Mckendree, Jean; Munro, Don; Powis, David
Abstract: Background : Over the past 70 years, there has been a recurring debate in the literature and in the popular press about how best to select medical students. This implies that we are still not getting it right: either some students are unsuited to medicine or the graduating doctors are considered unsatisfactory, or both. Aim : To determine whether particular variables at the point of selection might distinguish those more likely to become satisfactory professional doctors, by following a complete intake cohort of students throughout medical school and analysing all the data used for the students' selection, their performance on a range of other potential selection tests, academic and clinical assessments throughout their studies, and records of professional behaviour covering the entire five years of the course. Methods : A longitudinal database captured the following anonymised information for every student ( n = 146) admitted in 2007 to the Hull York Medical School (HYMS) in the UK: demographic data (age, sex, citizenship); performance in each component of the selection procedure; performance in some other possible selection instruments (cognitive and non-cognitive psychometric tests); professional behaviour in tutorials and in other clinical settings; academic performance, clinical and communication skills at summative assessments throughout; professional behaviour lapses monitored routinely as part of the fitness-to-practise procedures. Correlations were sought between predictor variables and criterion variables chosen to demonstrate the full range of course outcomes from failure to complete the course to graduation with honours, and to reveal clinical and professional strengths and weaknesses. Results : Student demography was found to be an important predictor of outcomes, with females, younger students and British citizens performing better overall. The selection variable "HYMS academic score", based on prior academic performance, was a significant predictor of components of Year 4 written and Year 5 clinical examinations. Some cognitive subtest scores from the UK Clinical Aptitude Test (UKCAT) and the UKCAT total score were also significant predictors of the same components, and a unique predictor of the Year 5 written examination. A number of the non-cognitive tests were significant independent predictors of Years 4 and 5 clinical performance, and of lapses in professional behaviour. First- and second-year tutor ratings were significant predictors of all outcomes, both desirable and undesirable. Performance in Years 1 and 2 written exams did not predict performance in Year 4 but did generally predict Year 5 written and clinical performance. Conclusions : Measures of a range of relevant selection attributes and personal qualities can predict intermediate and end of course achievements in academic, clinical and professional behaviour domains. In this study HYMS academic score, some UKCAT subtest scores and the total UKCAT score, and some non-cognitive tests completed at the outset of studies, together predicted outcomes most comprehensively. Tutor evaluation of students early in the course also identified the more and less successful students in the three domains of academic, clinical and professional performance. These results may be helpful in informing the future development of selection tools.